Migration in CIS in the context of European integration and changing socio-political borders - Uzagalieva, Ainura (2012)
Labor migration from Eastern Europe and Commonwealth of Independent States (CIS) to Western countries became an important socio-economic issue due to the large number of migrants. Since political systems and the nature of border management in these regions change, migration flows turned out to be a very complex and unpredictable issue. The purpose of this study is to analyze possible scenarios and demographic consequences of migration flows, paying particular attention to region specific factors and migration policies implemented in recent years. The paper attempts to bridge a gap in literature on this important topic, linking traditional labor market factors with uncertainty issues and policies implemented in migrant receiving countries within the CIS. Our findings suggest that economic and migration situation in the destination CIS members became a very important determinant of migration flows. In this respect, we employ a gravity model on the sample of 12 CIS members and estimate the potential size of migration flows under three migratory scenarios. Based on these scenarios, we further evaluate the demographic consequences of migration in the largest members, including Russian Federation, Ukraine and Uzbekistan which differ largely in terms demographic as well as economic and geographic conditions. The study reveals that further demographic ageing is inevitable over the next decades even if these three countries are not similarly affected. Indeed, the dependency ratio, or the ratio of retirees to the working population, should double. We conclude that reasonable migratory flows - economically motivated - will have no significant impact on these trends unless if they become substantial.